COVID-19 restrictions and consumers' psychological reactance toward offline shopping freedom restoration. Issue 13 (25th October 2020) - Akhtar, Naeem; Nadeem Akhtar, Muhammad; Usman, Muhammad; Ali, Moazzam; Iqbal Siddiqi, Umar
ABSTRACT: The COVID-19 pandemic threats and its subsequent restrictions on people's freedom, social interaction, closures of workplaces and shopping stores have caused public psychological reactance. In response, the study develops and tests a conceptual framework, which unveils the effects of perceived choice hesitation and perceived choice confidence on consumers' psychological reactance. It also corroborates two bipolar behavioral outcomes of consumers' psychological reactance— choice freedom satisfaction and resistance to persuasion. We employ the moderating role of anticipated worry and trust in government in strengthening the psychological reactance and final behavioral outcomes, respectively. Data collected from the country of origin of COVID-19 pandemic indicated the positive effects of antecedents on psychological reactance, which negatively affected choice freedom satisfaction and positively to resistance to persuasion. Anticipated worry and trust in government positively moderated these relationships. Findings extend the literature on psychology, service management, and consumer behavior, and suggest to government policymakers and store managers.